Climate Change and Individual Behavior: Considerations for Policy - Liverani, Andrea (Washington, DC: World Bank, 2012)
Climate change is anthropogenic - the product of billions of acts of daily consumption. That solutions need to be anthropogenic too is well accepted. Yet, suggested solutions are normally cast in the realms of finance and technology, often neglecting the primal root of the problem: individual behavior. An emerging body of social-psychology scholarship has examined the barriers and drivers of individual behavior in relation to both adaptation and mitigation. This paper reviews some of its conclusions, and suggests policy areas that should be considered in devising appropriate interventions.